Cardiac arrest due to intentional yew tree (Taxus baccata) ingestion - Dorota Ochijewicz; Anna Fojt; Jakub Zieniewicz; Robert Kowalik (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2022)
A 22-year-old woman with a history of bulimia, depression, and one suicidal attempt was admitted to the Emergency Department (ED) after out of hospital cardiac arrest. Her co-workers were proceeding with basic life support with an automated external defibrillator. After the arrival of the emergency service, advanced life support proceeded and ventricular fibrillation was the first rhythm recorded.